Synthetic polypeptides as antigens - Van Regenmortel, M. H. V. (Laboratory techniques in biochemistry and molecular biology, 1988)
Synthetic Polypeptides as Antigens is the first volume to give a comprehensive treatment under one cover of the various techniques used for synthesizing peptides by the solid phase approach, for coupling them to carrier molecules and analyzing their immunochemical activity by a variety of immunoassays. This book also describes methods for analyzing the antigenic structure of proteins and predicting the location of their antigenic sites. Recent advances in the detection of gene products with antipeptide antibodies, and the still controversial use of synthetic peptides as vaccines are also descr.